Prothrombotic Genetic Risk Factors and the Occurrence of Gestational Hypertension with or without Proteinuria - Grandone, Elvira; Margaglione, Maurizio; Colaizzo, Donatella; Cappucci, Giuseppe; Sciannamé, Natale; Montanaro, Sergio; Paladini, Dario; Martinelli, Pasquale; Minno, Giovanni Di (Thrombosis and Haemostasis, 1999)
Gestational hypertension with or without proteinuria is a multi-factorial disease in which the presence of a hypercoagulable state has been suggested. The prothrombin G20210A, the Factor V (FV) Leiden mutations, and the C677T 5-10 methylenetethrahydrofolate reductase (MTHFR) polymorphism were investigated in 140 women with gestational hypertension and in 216 normotensive women from Southern Italy. Nine controls (4.1%) and 16 cases (11.4%; OR: 2.96, 95% CI: 1.27-6.91) carried the prothrombin A20210 allele. FV Leiden mutation was observed in 4 controls (1.8%) and 11 cases (7.9%; OR: 4.53, 95% CI: 1.41-14.53). The TT MTHFR genotype was found in 36 controls (16.6%) and 34 cases (24.4%; OR: 1.61, 95%CI: 0.96-2.74). The impact of potential confounding variables was evaluated using a logistic regression analysis. Nulliparity, Factor V Leiden and prothrombin A20210 carrier status resulted to be independent risk factors of having gestational hypertension with or without proteinuria. Imbalance of haemostasis, through prothrombotic genetic factors, may predispose to the occurrence of gestational hypertension.